Application of Quantum Computing in Medical Imaging: Revolutionizing MRI and CT Scan Technology - Khalaf, Manar Hani; Adel, ELAF Abbas; Mohammed, Rawaa Hashim; Emaduldeen, Ali Ayad; Jasim, Baneen Lsmael (American Journal of Botany and Bioengineering, 2025)
Quantum computing has emerged as a transformative technology with the potential to revolutionize medical imaging, particularly Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) scans. Despite advancements in classical imaging systems, limitations in resolution, speed, noise reduction, and accessibility persist—especially in low-resource settings. This study explores how quantum algorithms, quantum-enhanced sensing, and quantum machine learning can address these challenges by enhancing image reconstruction, reducing noise, and accelerating data processing. Through literature analysis and case-based evaluation, the paper outlines how quantum computing can significantly improve imaging precision and diagnostic accuracy while lowering radiation exposure. The implications suggest a paradigm shift in healthcare diagnostics, requiring interdisciplinary collaboration and updated regulatory frameworks to ensure clinical adoption and patient-centered implementation.